The antioxidant effect of the Malaysian Gelam honey on pancreatic hamster cells cultured under hyperglycemic conditions - Batumalaie, Kalaivani; Qvist, Rajes; Yusof, K.M.; Ismail, Ikram Shah; Sekaran, Shamala Devi (Springer, 2013)
Type 2 diabetes consists of progressive hyperglycemia, insulin resistance, and pancreatic Î²-cell failure which could result from glucose toxicity, inflammatory cytokines, and oxidative stress. In the present study, we investigate the effect of pretreatment with Gelam honey (Melaleuca spp.) and the individual flavonoid components chrysin, luteolin, and quercetin, on the production of reactive oxygen species (ROS), cell viability, lipid peroxidation, and insulin content in hamster pancreatic cells (HIT-T15 cells), cultured under normal and hyperglycemic conditions. Phenolic extracts from a local Malaysian species of Gelam honey (Melaleuca spp.) were prepared using the standard extraction methods. HIT-T15 cells were cultured in 5 CO2 and then preincubated with Gelam honey extracts (20, 40, 60, and 80 Î¼g/ml) as well as some of its flavonoid components chrysin, luteolin, and quercetin (20, 40, 60, and 80 Î¼M), prior to stimulation by 20 and 50 mM of glucose. The antioxidative effects were measured in these cultured cells at different concentrations and time point by DCFH-DA assay. Pretreatment of cells with Gelam honey extract or the flavonoid components prior to culturing in 20 or 50 mM glucose showed a significant decrease in the production of ROS, glucose-induced lipid peroxidation, and a significant increase in insulin content and the viability of cells cultured under hyperglycemic condition. Our results show the in vitro antioxidative property of the Gelam honey and the flavonoids on the Î²-cells from hamsters and its cytoprotective effect against hyperglycemia.